Serious games for learning Korean language-hwaiting!! application - Siti Nurain, Mohamad Amin (2019)
The “Hwaiting!!” application helps learners acquire basic communicative skills in Korean languages by going through the combination of interactive lesson and interactive games that give user a concrete contexts in which to develop and apply their skills. Since the rapid growth of bilateral trade between Malaysia and South Korea, and the growing amount of Korean investments entering Malaysia have influenced the demand for people with expertise on Korea. Hence, the problem is education system in Malaysia did not include the Korean Language classes in the syllabus like Mandarin does, which make it difficult for them to learn. The objectives of this project is to design and develop a mobile serious games application that provide Korean language education for student. At the end of this project, this application will provide the excellent courseware, where user can easily learnt the basic and double consonants, basic and double vowels by listening to the audio, with the help of romanization, and also the conversation practice in term of greetings and shopping topics through the drag and drop activities, nice graphics and design, include multiple choice questions (MCQs) and also user-friendly. The User Acceptance Testing (UAT) had been used in order to get a feedback and find the pros and cons of the fully developed project. This article gives an overview of the application, and describes the experience to date in transitioning the application from prototype into training application using Addie Model methodology.